Peningkatan Temperature Jacket Cooling Fresh Water Pada Main Engine Di MV. Lumoso Karunia VIII - irfan, Irfanudin husni razzaq; Hermanto, Andy Wahyu; Pranyoto (Indonesian Journal of Marine Engineering, 2025)
The maritime transportation system plays a crucial role in international trade, with ships serving as the main means of transporting goods and passengers. One of the vital components in ship operations is the main engine, which requires a cooling system to maintain temperature stability. The jacket cooling fresh water system is the preferred choice because it can reduce the risks of corrosion and scale formation, which often occur in sea water-based cooling systems. The MV. Lumoso Karunia VIII's main engine fresh water cooling system overheated, reaching 90ºC and damaging the cylinder cover, which consequently disrupted operations. This study investigates the causes, effects, and preventative measures for this temperature spike in the engine's jacket cooling water system. A qualitative descriptive approach, using interviews and direct observation, was employed, with data analyzed using the SHEL model. Interviews were conducted with the chief engineer, second engineer, and fourth engineer. The factors causing overheating in temperature of jacket cooling fresh water in main engine include inadequate maintenance of the heat exchanger, blockage in the inlet that obstructs the flow of fresh water to the main engine, contamination in the cooling water, and dirt accumulation. The impact of the increased temperature in the jacket cooling fresh water of the main engine is engine overheating and financial losses. Efforts to prevent the overheating jacket cooling fresh water temperature in the main engine include regular maintenance and consistent inspections according to the Planned Maintenance System (PMS), cleaning of the heat exchanger and dirty expansion tank, as well as improving communication among the crew in managing the maintenance of the cooling system.